Hubris et péché des origines : remarques sur le cas de Grégoire de Nazianze - Jean-Marie Mathieu (Kentron, 2006)
This paper is a postscript to J.-M. Mathieu’s article “Hybris-démesure ? Philologie et traduction” (Kentron, 20, 2004, 15-45), with special reference to Greek Patristics and Gregory of Nazianzus. It adds two ideas to it. (1) The meaning of the word ὕβρις, as defined by Gregory of Nazianzus, is not religious but moral and social (C I ii 34, 100-101). Indeed the use of the word by Gregory of Nazianzus (nearly three hundred occurrences), is congruent with the following meaning: a word, or an act, at which the victim incurs shame. (2) Neither is there, according to the same Father, any hubris, in the religious meaning of the English word, committed by the first human being in Paradise. God planned to divinize Man, and to use him in the ultimate divinization (C I i 8, 98-99; C I ii 10, 134-144; etc.). Adam’s case is different from Lucifer’s: for Man, there was no presumption in seeking to acquire the attributes of God. Excess, or lack of measure, was for the new-born Adam, urged by Lucifer, to act before time (προώριος, etc.: C I i 8, 114 and 120, etc.).